(untitled) (PerCursos, 2025)
This essay presents and discusses the relationships between media and sports, mediated by technological apparatuses. By understanding phenomena that attribute control over meanings to the media – such as the symbolic power conferred upon them – we propose a reflection on sport as an aesthetic artifact within the media-sport universe. We observe continuities (e.g., the traditional model of sports transmission and the emphasis on the logic of infotainment to the detriment of the informational model) and deepening dynamics involving media and sport (such as the participation of betting companies in the sports context; the presence of virtual influencers; and other forms of transmission beyond traditional television formats, including free-to-air, pay TV, and now virtual spaces like YouTube and social media). Mediatization, spectacularization, and commodification are intrinsically considered through the lens of sport as a cultural product/artifact that is appropriated for media transformations. Thus, the text aims to analyze how sport has been used as an aesthetic artifact in the media-sport context, reflecting on the cultural and social transformations resulting from its spectacularization by the media. Finally, we pose a set of questions that could form a research agenda, considering the new configurations of the sports spectacle.